General Sambo's Atrocities The Main Duties of The State Police of The Republic of Indonesia - Junaedi (Journal Social Civilecial, 2023)
Article 27 Paragraph (1) of the 1945 Constitution reads, "All citizens have the same position in law and government and are obliged to uphold the law and government without exception". Law Number 2 of 2002 concerning the Police Article 2 of Law Number 2 of 2002 concerning the National Police of the Republic of Indonesia explains that the police are one of the functions of the state government in the field of maintaining security and public order, law enforcement, protection, protection and service. To society. Therefore, General Ferdy Sambo's cruelty was in contrast to the primary duties of the Indonesian National Police. The president's order to quickly, transparently, and accountably disclose this case in the case of Brigadier Nofriansyah Yosua Hutabarat (Brigadier J), the National Police Chief, has also deactivated 3 (three) officers in this case. They are the Head of the Profession and Security Division (Kadiv Propam), Inspector General Ferdy Sambo, Head of the Internal Security Bureau (Karo Paminal), Brigadier General Hendra Kurniawan, and Head of the South Jakarta Resort Police (Kapolres) Chief Commissioner of Police (Kombespol) Budhi Herdi. Formation of a Special Team consisting of Commissioner General of Police (Komjenpol) Gatot Eddy Pramono, assisted by Inspector of General Supervision of the National Police Commissioner General of Police (Komjen Pol) Agung Budi Maryoto, Head of the National Police Criminal Investigation Agency (Kabareskrim) Commissioner General of Police (Komjenpol) Agus Andrianto, National Police Agency Intelligence and Security of the Indonesian National Police Commissioner General of Police (Komjenpol) Ahmad Dofiri, and Assistant Human Resources Inspector General of Police (Irjenpol) Wahyu Widada, work in charge of investigating the crime scene (TKP), autopsy results as well as statements of several witnesses based on scientific crime investigation until the results are objective and are open to the public. Assigning a suspect to Ferdy Sambo as stated in Article 340 concerning premeditated murder, which is subsidiary to Article 338 in conjunction with Articles 55 and 56 of the Criminal Code (KUHP), with the punishment for premeditated murder is the death penalty.